Competences for Economic Diplomacy and International Business; Convergence or Divergence? - Marjan Svetličič (Central European Public Administration Review)
The article discusses whether competences needed for effective contemporary economic diplomacy are different from or similar to those needed by international businessmen, and whether economic diplomats are capable of responding to the challenges of tectonic changes in the world with the competences they now possess. It concludes that a convergence of competences between economic diplomats and international businessmen is taking place; diplomats are increasingly using competences of international managers, and international manages increasingly need diplomatic skills. Special attention is given to: relations between internal and international economic relations, the need for global mindsets, the business intelligence role of economic diplomats and long-term planning. Competences of economic diplomats from small countries are different from those of their large-country counterparts. One basic competence is flexibility, the readiness to change and to adjust to changes. To adjust to changes, there is also a need for reforms in training of economic diplomats and international businessmen.